Molecular Docking of Brassicasterol Inhibition from Green Mustard Plant (Brassica Chinensis Var. Parachinensis) with Cytochrome P450 in Treating Chagas Disease - Suryani, Okta; Fahira, Ade Irma (Sains Natural: Journal of Biology and Chemistry, 2024)
The aim of this study was to evaluate the potential of brassicasterol found in mustard greens as a cytochrome P450 inhibitor using a computational approach. The research method involved the use of various software such as PyRx, Pymol, Protein Plus, Protein Data Bank (PDB), and Lipinski's rule to analyze the molecular interactions and physicochemical characteristics of brassicasterol. The analysis results showed that brassicasterol has a significant affinity for cytochrome P450, with binding affinity values reaching -8.5, -8.4, and -8.2. RMSD analysis also showed that the brassicasterol-cytochrome P450 complex showed good stability, with RMSD values ranging from 0 to 2.832. The use of Protein Plus software illustrated the interaction between brassicasterol and cytochrome P450, while Lipinski analysis showed that brassicasterol meets the expected physicochemical criteria to be a chagas disease drug candidate, such as a molecular mass of 353, having one hydrogen bond donor and acceptor, and having a log P of 2.2 and a molar reactivity of 99.08. These findings provide new insights into therapeutic development in treating chagas disease using mustard green extract and brassicasterol as a cytochrome P450 inhibitor, but further study is needed to verify the potential of brassicasterol as a chagas disease drug.